1993
DOI: 10.1021/jm00074a010
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted dibenzoxazepines as analgesic PGE2 antagonists

Abstract: 8-Chlorodibenz[b,f][1,4]oxazepine-10(11H)-carboxylic acid, 2-acetylhydrazide (1, SC-19220) has been previously reported by us and others to be a PGE2 antagonist selective for the EP1 receptor subtype with antinociceptive activities. Analogs of SC-19220, in which the acetyl moiety has been replaced with pyridylpropionyl groups and their homologs, have been synthesized as illustrated by compounds 13 and 29. These and other members of this series have been shown to be efficacious analgesics and PGE2 antagonists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 4 publications
2
43
0
Order By: Relevance
“…Both EP1 receptor antagonists (16)(17)(18) and EP1 knockout mice exist, but have not been characterized in models of hypertension. While conventional targeting of the gene encoding EP1 in mice suggests a role for EP1 in maintaining basal blood pressure (19), interpretation of these data is complicated by the circumstance that the EP1 locus encompasses a second gene on the antiparallel strand, the serine/ threonine protein kinase N (PKN) (20).…”
Section: Introductionmentioning
confidence: 99%
“…Both EP1 receptor antagonists (16)(17)(18) and EP1 knockout mice exist, but have not been characterized in models of hypertension. While conventional targeting of the gene encoding EP1 in mice suggests a role for EP1 in maintaining basal blood pressure (19), interpretation of these data is complicated by the circumstance that the EP1 locus encompasses a second gene on the antiparallel strand, the serine/ threonine protein kinase N (PKN) (20).…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine whether EP1 receptors are also involved, the EP1 receptor antagonist SC-51089 [32][33][34] was employed. Initially, the effect of increasing concentrations of SC-51089 on the stimulatory effect of 0.028 μM PGE 1 was examined.…”
Section: Pge 1 Stimulation Of the β1 Promoter: Signaling Through Ep1 mentioning
confidence: 99%
“…Studies which were aimed to identify key structural requirements to synthesize EP selective agonists and/or antagonists and to provide insights to the mechanism of receptor ligand selectivity revealed that sensitive positions for agonist-activity at the EP1 receptor is the hydroxyl group at the carbon 15 position and C-1 carboxylate [29]. The selective EP1 antagonists may aid in characterization of the effects mediated by this receptor subtype [30][31][32]. The reported selective EP1 receptor antagonists are the acylhydrazide derivative SC51322 (by Searle group) [31], ZD6416 (by AstraZeneca) [33,34], ONO-8713 (by Ono) [35] and thiophene derivative ((by Merck Frosst) [36].…”
Section: Introductionmentioning
confidence: 99%
“…The selective EP1 antagonists may aid in characterization of the effects mediated by this receptor subtype [30][31][32]. The reported selective EP1 receptor antagonists are the acylhydrazide derivative SC51322 (by Searle group) [31], ZD6416 (by AstraZeneca) [33,34], ONO-8713 (by Ono) [35] and thiophene derivative ((by Merck Frosst) [36]. Studies revealed that EP1 receptor plays a central role in PGE2-mediated allodynia [37,38] and inflammatory pain [39].…”
Section: Introductionmentioning
confidence: 99%